Chronic Uterine Inversio due to Myoma Geburt - Bobby Indra Utama, SpOG(K) (Andalas Obstetrics and Gynecology Journal, 2020)
Background : Uterine inversion is a rare obstetric emergency but potentially serious complication of labour. This disease characterized by severe pain and can cause life threatening condition. If these not immediately identified, the massive and underestimated blood loss can lead to hypovolemic shock. There for, early diagnosis and management of this condition is desirable.